Rethinking the measurement of household inflation expectations: Preliminary findings - Wilbert van der Klaauw; Wändi Bruine de Bruin; Giorgio Topa; Simon Potter; Michael Bryan (Federal Reserve Bank of New York, 2008)
This paper reports preliminary findings from a Federal Reserve Bank of New York research program aimed at improving survey measures of inflation expectations. We find that seemingly small differences in how inflation is referred to in a survey can lead respondents to consider significantly different price concepts. For near-term inflation, the 'prices in general' question in the monthly Reuters/University of Michigan Surveys of Consumers can elicit responses that focus on the most visible prices, such as gasoline or food. Questions on the 'rate of inflation' can lead to responses on the prices that U.S. citizens pay in general-an interpretation, or concept, closer to the definition of inflation that economists have in mind; they also lead to both lower levels of reported inflation and to lower disagreement among respondents. In addition, we present results associated with new survey questions that assess the degree of individual uncertainty about future inflation outcomes as well as future expected wage changes. Finally, using the panel dimension of the surveys, we find that individual responses exhibit considerable persistence, both in the expected level of inflation and in forecast uncertainty. Respondents who are more uncertain make larger revisions to their expectations in the next survey.
Keywords: E31; C81; E60; E66; 330; Inflation expectations; survey measurement